2013
DOI: 10.1161/circresaha.113.302052
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Raet1e , a Major Histocompatibility Complex Class 1–Like Molecule, Underlies the Atherosclerosis Modifier Locus Ath11 10b

Abstract: Rationale Quantitative trait locus mapping of an intercross between C57.Apoe−/− and FVB.Apoe−/− mice revealed an atherosclerosis locus controlling aortic root lesion area on proximal chromosome 10, Ath11. In a previous work, subcongenic analysis showed Ath11 to be complex with proximal (10a) and distal (10b) regions. Objective To identify the causative genetic variation underlying the atherosclerosis modifier locus Ath11 10b. Methods and Results We now report subcongenic J, which narrows the 10b region to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…17,18 There is growing evidence indicating that SGK1 is heavily expressed in macrophages and plays an important role in cellular migration. 28,30 Although inflammatory infiltration of the vascular wall by immigrating monocytes and monocytederived macrophages is critical to the development of atherosclerosis and although SGK1 is considered a candidate gene fostering the development of atherosclerosis, 31 nothing is hitherto known about the influence of SGK1 in atherogenesis.…”
mentioning
confidence: 99%
“…17,18 There is growing evidence indicating that SGK1 is heavily expressed in macrophages and plays an important role in cellular migration. 28,30 Although inflammatory infiltration of the vascular wall by immigrating monocytes and monocytederived macrophages is critical to the development of atherosclerosis and although SGK1 is considered a candidate gene fostering the development of atherosclerosis, 31 nothing is hitherto known about the influence of SGK1 in atherogenesis.…”
mentioning
confidence: 99%
“…Validation experiments implicated a SNP within the Raet1e (retinoic acid early transcript 1E) promoter that influences its expression. 71 Through initial characterization of phenotypic differences in congenic C57BL/6 and FVB/N Apoe À/À strains, linkage analysis of a cross between these strains, generation of FVB/N-Chr10 congenic strains, and functional validation experiments, these studies successfully identified Raet1e as a modifier for atherosclerosis severity resulting from ApoE deficiency. Mutagenesis screening is another strategy used to identify modifier genes in mice.…”
Section: Strategies To Identify Genetic Modifiers In Micementioning
confidence: 99%
“…They also demonstrate that modifier variants often occur within protein-coding exons, but may alternatively affect regulatory regions such as UTRs or promoters. 71 There does not appear to be a general mechanism by which modifier alleles are generated. Rather, any sequence variation affecting a gene's function in a way that impacts its interaction with other genes and networks may manifest as a modifier allele, depending on co-inheritance with an appropriate target allele and environmental context.…”
Section: Features Of Modifier Genes Nature Of Sequence Variationmentioning
confidence: 99%
“…In very few cases has a particular gene been identifi ed by this approach. However, recently the subcongenic analysis of the Ath11 locus in a cross between C57BL/6 Apoe −/− and FVB Apoe −/− mice has identifi ed a single gene, Raet1e encoding a major histocompatibility class 1-like molecule, whose expression level regulates aortic root atherosclerosis [ 71 ]. This conclusion was confi rmed by the targeted overexpression of one of the alleles of this gene, resulting in the predicted atherosclerosis phenotype.…”
Section: Genetics Of Murine Atherogenesismentioning
confidence: 99%